Genetics of the resistance to yellow rust (Puccinia striiformis f. sp. tritici) in varieties of bread wheat (Triticum aestivum L.) cultivated in Bajío - Huerta Espino, Julio; Torres García Rocío; Rodríguez García María Florencia; Villaseñor Mir Héctor Eduardo; Leyva Mir, Santos Gerardo; Solís Moya Ernesto (Revista Mexicana de Ciencias Agrícolas, 2018)
The varieties of bread wheat, Cortázar s94, Bárcenas S2002, Urbina S2007 y Maya S2007 were liberated for planting under irrigated conditions in “El Bajío”. These varieties maintain a resistance to different races of yellow rust that were found in the country; however, the genetic bases of resistance are unknown. To determine the genetics of the resistance, these varieties were crossed with the susceptible parent ‘Avocet- YrA’, and the determination of similitude of the genes was conducted through allele testing. The four varieties and the families F3 of each cross was evaluated during the summer of 2009 in the Experimental Field ‘Valle de Mexico’, Chapingo, Mexico State, under an artificial epiphyte created with the isolation MEX96.11. With the results of the evaluation of the families F3, it was determined that the resistance of the adult plant to yellow rust in Cortázar S94, Bárcenas S2002 y Maya S2007 is conditioned for two or three genes of additive effects, while in Urbina S2007, the resistance is conditioned for three or four genes of the same composition. The absence of complete acceptable families in the crosses between resistant varieties indicates the existence of at least one gene of resistance in common.